Methodological instructions for independent work on the discipline "Social labor relations in the organization of accounting activities" - Yurieva, Iryna (National Technical University "Kharkiv Polytechnic Institute", 2024)
Social and labor relations in the organization of accounting activities are a crucial element of any economic system. Therefore, the research of the theoretical foundations of social and labor relations regulation in countries with a developed market economy is an urgent issue for Ukraine – analysis of research and publications. Scientific works of scientists such as Butynets F. F., O. Grishnova, Ilyich L. M., A. M. Kolot, V. V. Sychova, and others are devoted to studying the problems of regulation of social and labor relations. However, despite the large number of scientific investments, this topic remains relevant and requires further research. These Methodological instructions for implementing independent individual analytical research work (reports) are part of the Methodological instructions for independent study of the discipline "Social and labor relations in the organization of accounting activities."
Keywords: methodological instructions; economic activity; finance; labor market; social partnership; auditing; International Labor Organization